2004
DOI: 10.1097/01.wcb.0000110049.43905.ac
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Erythropoietin-induced Brain Protection in Neonatal Hypoxia-Ischemia Rat Model

Abstract: Summary: Erythropoietin, a hemotopoietic growth factor, has brain protective actions. This study investigated the mechanisms of Recombinant Human EPO (rhEPO)-induced brain protection in neonates. An established rat hypoxia-ischemia model was used by ligation of the right common carotid artery of 7-day-old pups, followed by 90 minute of hypoxia (8% 0 2 and 92% N 2 ) at 37°C. Animals were divided into three groups: control, hypoxia-ischemia, and hypoxia-ischemia plus rhEPO treatment. In rhEPO treated pups, 300 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 81 publications
7
69
2
3
Order By: Relevance
“…We did not detect any significant alteration in EpoR expression in the ischemic cortex from 1 to 7 d after focal ischemic insult in the Epo-treated pups compared with vehicle-treated pups. This issue is consistent with the findings that Epo treatment does not alter EpoR mRNA levels in a neurotoxic model (12) and that Epo application for 3 d does not down-regulate EpoR in a neonatal hypoxic-ischemic model (28). Recent data have also shown that carbamylated Epo or certain Epo mutants do not bind to the classical EpoR, but these Epo mutants were neuroprotective in vitro and in vivo (42).…”
Section: Epo Improves Neonatal Focal Strokesupporting
confidence: 80%
See 2 more Smart Citations
“…We did not detect any significant alteration in EpoR expression in the ischemic cortex from 1 to 7 d after focal ischemic insult in the Epo-treated pups compared with vehicle-treated pups. This issue is consistent with the findings that Epo treatment does not alter EpoR mRNA levels in a neurotoxic model (12) and that Epo application for 3 d does not down-regulate EpoR in a neonatal hypoxic-ischemic model (28). Recent data have also shown that carbamylated Epo or certain Epo mutants do not bind to the classical EpoR, but these Epo mutants were neuroprotective in vitro and in vivo (42).…”
Section: Epo Improves Neonatal Focal Strokesupporting
confidence: 80%
“…In neonatal animals, Epo has been shown to reduce neurotoxicity of N-methyl-Daspartate receptor antagonists (12) and prevent brain injury in a P7 hypoxic-ischemic rat model (13,14,28) when the first dose is given before producing the injury. There are two important differences between our current study and previous ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in neonatal or adult rats after focal brain ischemia, brain trauma or experimental autoimmune encephalomyelitis systemic or intraperitoneal administration of exogenous EPO is neuroprotective [52,89,90]. Intravenously administered EPO also provides protection in animal models for spinal cord injury with improved functional neurological status [91,92].…”
Section: Intravenous/intraperitoneal Epo Administrationmentioning
confidence: 99%
“…Erythropoietin treatment reduces apoptotic cell death (Sun et al, 2004) and brain edema (Brissaud et al, 2010) and has an anti-inflammatory effect in the HI brain (Juul et al, 2009). It affects regenerative processes, promoting an increase in functional revascularization, in NSPC proliferation in the SVZ and in the number of new neurons that migrate to the striatum and to the cerebral cortex (Iwai et al, 2007).…”
Section: Boosting the Endogenous Regenerative Capacity Of The Neonatamentioning
confidence: 99%